Screen time impairs the relationship between physical fitness and academic attainment in children - Macarena M. Aguilar; Felipe A. Vergara; Erikson J.A. Velásquez; Raquel Marina; Antonio García-Hermoso (Elsevier, 2015)
OBJECTIVE: The purpose of this study was twofold: to analyze the association between physical fitness and academic attainment, and to determine the influence of screen time on the association between physical fitness and academic attainment.METHODS: A cross-sectional study including 395 schoolchildren from seven schools of the Maule Region, Chile (mean age 12.1 years; 50.4% boys) participated in the autumn of 2014 (March to June). Self-reported physical activity and screen time were evaluated. The study measured academic achievement (mean of the grades obtained in several core subjects), physical fitness (cardiorespiratory fitness and muscular strength), weight, height, parental education, and socioeconomic status. Linear regression analysis was used to analyze the relationships between physical fitness and academic attainment after adjusting for potential confounders by gender. Analysis of variance was used to analyze the differences in academic attainment according to fitness and screen time categories (< 2 hours/day and ≥ 2 hours/day).RESULTS: In both genders good cardiorespiratory fitness levels were associated with high language (ß = 0.272-0.153) and mean academic attainment (ß = 0.192-0.156) grades; however, after adjusting for screen time and other potential confounders, these associations disappear. Similarly, no relationship was observed after analyzing those children who spend more hours of screen time (≥ 2 hours/day).CONCLUSIONS: Academic attainment is associated with higher cardiorespiratory fitness levels; however, it was weakly impaired by screen time. These findings seem to suggest that parents and policymakers should minimize the negative effects of screen time on children's lives to maximize the beneficial effect of healthy habits on academic attainment.